Primary iliocaval leiomyosarcomas: The path beyond surgery. Issue 5 (May 2020) - Ong, Chin-Ann J.; Smith, Myles J.; Snow, Hayden A.; Benson, Charlotte; Jones, Robin L.; Hayes, Andrew J.; Strauss, Dirk C.
Abstract: Introduction: Iliocaval leiomyosarcoma (ICLM) is a rare and aggressive form of sarcoma within the retroperitoneum. Surgery is the mainstay of treatment, with no consensus on the benefit of chemoradiotherapy in the neo/adjuvant setting. This study aims to describe the natural history of a chemotherapy-naïve ICLM treated in a tertiary cancer centre and to explore potential directions to improve oncological outcome. Materials and methods: A prospective database was used to identify patient demographics, clinicopathological variables and oncological outcomes in 30 patients who underwent surgical resection in our institution for primary non-metastatic ICLM between 2003 and 2018. Results: There was no 90-day mortality. With a median follow-up time of 70.0 months (95% CI 52.6–87.4), 5/30 patients (16.7%) developed local recurrence while 11/30 (36.7%) developed distant metastatic disease. 1 patient (3.3%) developed both local and distant recurrence. Median overall survival of our cohort was 41.0 months (95% CI 33.6–48.4) and 5-year overall survival rate was 32.1%. Multivariate survival analysis using the Cox proportional hazard model identified tumour grade and blood loss of more than 600 mL as key prognostic factors in our model. Conclusion: Management of ICLM should be centralised in high-volume sarcoma centres with expertise in the management of retroperitoneal sarcomas. Integration of tumour biology with a concerted effort to conduct conclusive multi-centre phase III in histological and molecularly defined sarcoma subgroups is necessary to improve patient outcome. We eagerly await the results of STRASS 2 study to gain more insights to the efficacy of neoadjuvant chemotherapy on patient prognosis.